SDGs trade-offs associated with voluntary sustainability standards: A case study from the coffee sector in Costa Rica - Karla Rubio-Jovel; Jorge Sellare; Yannic Damm; Thomas Dietz (Sustainable Development, 2023)
The transition toward a more sustainable agricultural production has become an essential step in achieving the sustainable development goals (SDGs), launched by the United Nations in 2015. Voluntary sustainability standards (VSS) have been proposed as a useful governance tool for guiding this transition. Thus, this article uses a case study from the coffee sector in Costa Rica to assess the contribution of VSSs to the achievement of the SDGs. We rely on panel data from coffee producers captured between 2017 and 2019 to carry out this assessment. Results of the statistical analysis suggest that VSSs alone are not enough to promote a transition to a more sustainable coffee production, as trade-offs between the contributions of VSSs to the different SDGs emerge. If the VSSs are to promote sustainable practices among producers while ensuring socioeconomic benefits for producers, workers, and their families, implementation modifications are required.
Keywords: 330; certification; coffee; sustainable development goals; trade-offs; voluntary sustainability standards